Foreign Direct Investment (FDI) and Economic Development Impacted by Peru's Public Policies - Rodríguez-Saavedra, Miluska Odely; Chávez-Quiroz, Felipe Gustavo; Quispe-Nina , Wilian; Caira-Mamani, Rocío Natividad; Medina-Esquivel, Wilfredo Alexander; Tapia-Meza, Edwing Gonzalo; Romero-Carazas, Rafael (Journal of Ecohumanism, 2024)
The purpose of this research is to relate foreign direct investment (FDI) and economic development as impacted by public policies in Peru. The methodological design was non-experimental, cross-sectional, correlational, with a qualitative approach. The technique was the survey and its instrument was a questionnaire. The population grouped the 53 countries that invested in Peru into 815 companies and 5 public entities comprising 46 public officials. The results show a very strong, positive and favorable correlation between the variables analyzed of 0.936 and with a sig value of 0.001 the hypothesis of the study was proved. Likewise, in the SPSS results it was possible to correlate a binding connection between the latent variables FDI and economic development of (0.42 and 0.58) Economic development and public policies of (0.62 and 0.05) Public policies and FDI of (0.08 and 0.06). In conclusion, it is established that FDI is a significant determinant of economic growth, with public policies playing a central role in modulating this effect.